Carob pulp syrup : a potential Mediterranean carbon source for carotenoids production by Rhodosporidium toruloides NCYC 921 - Martins, Vasco (2019)
ABSTRACT: Carob pulp syrup (CPS) was used as carbon source to produce carotenoids from Rhodosporidium toruloides. To increase the carbon concentration in the growth medium aiming at the carotenoid production improvement, the CPS was concentrated and two different total sugar (TS) concentrations (195.6 g/L and 548.7 g/L) were studied. CPS 195.6 g/L TS contained 4.1 g/L and 0.7 g/L of hydroxymethyl furfural (HMF) and furfural, respectively. CPS 548.7 g/L TS contained 17.7 g/L of HMF and 1.2 g/L of furfural, respectively. >42% of metabolically active cells (with intact membrane and enzymatic activity) were detected throughout the course of the yeast cultivation on CPS 195.6 g/L TS. On the contrary, the proportion of metabolically active cells was always below 28% during the yeast cultivation on CPS 548.7 g/L TS. Nevertheless, the maximum carotenoid content and productivity (0.42 mg/g and 0.43 mg/Lh, respectively) were obtained when using CPS 548.7 g/L TS.